Lattice distortion and magnetic property of high entropy alloys at low temperatures. (30th March 2022) - Tan, Yuan-Yuan; Chen, Zhong-Jun; Su, Ming-Yao; Ding, Gan; Jiang, Min-Qiang; Xie, Zhou-Can; Gong, Yu; Wu, Tao; Wu, Zhong-Hua; Wang, Hai-Ying; Dai, Lan-Hong
Highlights: We carry out in situ SR-XRD experiments and magnetic measurements of CrCoNi MEA, CrFeCoNi and CrMnFeCoNi HEAs to investigate their lattice distortion and magnetic property evolutions with temperature from 293 to 123 K and 293 to 5 K, respectively. We observe linear lattice contraction and a general reduction of local lattice distortion, and its variation tendency is in well agreement with the reported temperature dependency of stacking fault energy (SFE). It is striking to find a paramagnetic to ferromagnetic transformation of CrFeCoNi HEA at cryogenic temperature, suggesting it as a promising candidate for soft magnetic materials. Our findings suggest reductions of lattice distortion with temperature possibly making a critical contribution to twinning at low temperature. Magnetic measurements demonstrated none obvious correlation between magnetizations of the three alloys and their deformation behaviors. Abstract: Deformation mechanisms and magnetic properties of medium and high entropy alloys (MEA/HEAs) closely relate to lattice distortion and are strongly temperature-dependent, in particular, at low temperature ranges. However, little attention has been paid to the evolution of lattice distortion with temperature decreasing and its effects on deformation behavior and magnetic state transition. In this work, we carry out in situ synchrotron radiation based X-ray powder diffraction (SR-XRD) experiments from 293 to 123 K aiming for determining lattice distortion evolutions of CrCoNi MEA, CrFeCoNi and CrMnFeCoNi HEAs. Magnetic measurements at corresponding low temperatures and cryogenic ranges are further conducted. The in situ SR-XRD results demonstrate a general reduction of lattice distortion magnitude with temperature decreasing, which shows a similar tendency with that of reported stacking fault energy (SFE) values. It is thus suggested that lattice distortion reduction possibly makes a critical contribution to deformation mechanism transition. The magnetic measurement results show a clear ferromagnetic transition of CrFeCoNi HEA when temperature is below 173 K. While, no obvious magnetic state transition is observed for CrCoNi MEA and CrMnFeCoNi HEA. The present findings on lattice distortion evolutions will pave the way for designing targeted HEAs with particular properties.